229k views
1 vote
Find the inverse function of y=(x-2)^2 + 3. please show steps

User Mstfdz
by
5.5k points

1 Answer

6 votes

Answer:


f^(-1)(x)=2\pm√(x-3)

Explanation:

we have


y=(x-2)^2+3

step 1

Exchange the variables (x for y and y for x)

so


x=(y-2)^2+3

Isolate the variable y

step 2


x=(y-2)^2+3

subtract 3 both sides


(y-2)^2=x-3

step 3

square root both sides


y-2=\pm√(x-3)

step 4

Adds 2 both sides


y=2\pm√(x-3)

step 5

Let


f^(-1)(x)=y


f^(-1)(x)=2\pm√(x-3)

User Dafang Cao
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.